Pengembangan LKPD Etnomatematıka Berbasıs Rme Untuk Menıngkatkan Lıterası Matematıka Sıswa - Husnul Khatimah; Nunung Fatimah (Jurnal Elementaria Edukasia, 2023)
This research is research into the development of RME-based ethnomathematics LKPD to improve elementary school students' mathematical literacy skills which aims to produce ethnomathematics LKPD products using the RME approach to improve students' numeracy literacy that is valid, effective and practical. This research is development research whose product is expected to improve the mathematical literacy skills of elementary school students. This research method uses the research and development (RnD) method which is often called the development method. The development model used in this research is the ADDIE development model. The ADDIE model consists of 5 stages, namely the analysis stage, design stage, development stage, implementation stage and evaluation stage. The research results show that RME-based ethnomathematics worksheets can improve students' numeracy literacy skills with effective student activities shown by each indicator observed according to a tolerance of 10%. Student responses to the LKPD were positive and reached above 80%. And classical learning completeness was achieved with a percentage of 95%. The teacher's ability to manage learning has good criteria with an observer assessment for each indicator of at least 3.